An Exploratory Study of Fact-Checking Practices in Conflict and Authoritarian Contexts - Samba Dialimpa Badji; Kristin Skare Orgeret; Bruce Mutsvairo (Media and Communication)
This study explores fact-checking practices in Ethiopia and Mali in times of conflict and in a context marked by increasing restrictions to press freedom. The objective is to understand how, in this hostile environment, fact-checkers in these two countries manage to carry out their activities. Our findings reveal that fact-checkers are often victims of online bullying and harassment and fear reprisal from governments. This pushes them to self-censor, avoiding working on sensitive topics, such as military issues in Mali. In addition, fact-checking organizations in both countries highlight the difficulty of accessing reliable sources. Consequently, they focus more on debunking viral social media content, thus effectively becoming content moderators who have turned away from the mission of holding leaders accountable, one of the primary functions of fact-checking. Regarding their role conception, fact-checkers in Ethiopia and Mali see themselves more as guides helping navigate the information disorder than “guardians of truth” or “truth keepers.”